Revitalisasi Dakwah Islam: Toleransi, Harmonisasi, dan Moderasi - syahirul alim (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2020)
Islamisation is sometimes interpreted as a religious mission to balance Christianisation which is closely related to the missionary aspects of religions. Islamisation or Islamic da'wah activities are tolerant, moderate and harmonious, taking into account humanitarian aspects in many ways. The long history of Islamisation throughout the world shows that Islam is a tolerant religion in which the process of religious conversion is carried out voluntarily and peacefully. Islamisation in the Archipelago is the best example of a successful da'wah activities in the conversion of Islam both individually and collectively. Muslim missionaries in the Archipelago are intellectual sufism figures who have the usual broad ability to revitalize da'wah into rational, reformist and progressive manner.